Analysis of solar desalination system using heat pump - Amin, Zakaria Mohd.; Hawlader, Mohammad Nurul Alam (Elsevier, 2015)
This paper investigates a pilot desalination system which consists of a direct expansion solar assisted heat pump (DXSAHP) coupled to a single-effect evaporator unit. The working fluid used is R134a and distillate is obtained via falling film evaporation and flashing in the unit. Experiments have been conducted in both day and night meteorological conditions in Singapore and the effects of solar irradiation and compressor speed have been studied against the system performance. From the experiments, the Performance Ratio (PR) obtained ranges from 0.43 to 0.88, the average Coefficient of Performance (COP) was 8 and the highest distillate production recorded was 1.38 kg/h.